Prescribing of clotrimazole-betamethasone dipropionate, a topical combination corticosteroid-antifungal product, for Medicare part D beneficiaries, United States, 2016-2022 - Dustin W. Currie; Avrom S. Caplan; Kaitlin Benedict; Kelly M. Hatfield; Dallas J. Smith; Shari R. Lipner; Jeremy A.W. Gold (Cambridge University Press, 2024)
During 2016-2022, Medicare part D beneficiaries filled 8,674,460 clotrimazole-betamethasone dipropionate prescriptions. Annual rates were stable (30.9 prescriptions/1,000 beneficiary-years in 2022, enough for one in every 33 beneficiaries). Diagnostic testing was infrequent, particularly among internal medicine, family medicine, and general practitioners, suggesting potential opportunities to improve diagnostic and prescribing practices.